Factors Influencing the Financial Management Behavior of PayLater Users - Putri, Sari Widyaningtyas; Ayatulloh Michael Musyaffi; Gentiga Muhammad Zairin (LPPM Universitas Negeri Jakarta, 2024)
The purpose of this study was to examine the effect of financial literacy, financial socialization, and financial self-efficacy on the financial management behavior of PayLater users in the Jabodetabek area. The sampling method uses convenience sampling. Data collection uses a survey method by distributing questionnaires. In this study, 100 respondents were obtained who met the criteria with statistical analysis using Structural Equation Modeling - Partial least square (SEM - PLS). The results showed that the three independent variables had an effect on financial management behavior. From the research results, it is hoped that paylater users will improve their financial understanding and learn to manage finances wisely, such as making financial plans, paying paylater bills on time, and limiting themselves in using excess paylater. Good financial management behavior can prevent individuals from financial problems and the risk of defaulting on paylater bills.